The protective effects and mechanisms of rosmarinic acid against Pseudomonas aeruginosa infection in Caenorhabditis elegans - Zhang, Ying; Shu, Chengjie; Li, Zhuohang; Qu, Man; Wang, Chunwu; Nie, Shihui; Xu, Qijiang; Gu, Shunlin; Fan, Mingjie; Shi, Baojun; Fu, Lei; Zhang, Fenglun (Frontiers in Pharmacology, 2025)
IntroductionPseudomonas aeruginosa poses a significant risk to both the environment and organisms. Although the natural compound rosmarinic acid (RA) has demonstrated considerable antibacterial properties, its efficacy in combating P. aeruginosa infection remains vague.MethodsUsing Caenorhabditis elegans as an infection model, we evaluated the damage induced by PA14, examining indicators including lifespan, locomotor behavior, pharyngeal pumping, excretion cycle, lipofuscin, reactive oxygen species (ROS), as well as mitochondrial membrane potential (MMP) and the expression of mitochondrial-related genes mev-1 and gas-1.ResultsPA14 infection had a diverse effect on C. elegans, including reduced lifespan, impaired behavioral functions (diminished head thrashing frequency, body bending frequency, and pharyngeal pumping frequency, as well as a prolonged excretion cycle), increased lipofuscin and ROS accumulation, and mitochondrial dysfunction (lower MMP and ATP content). RA treatment at concentrations of 100-300 mg/L dose-dependently reduced the number of PA14 colonies in the nematodes, prolonged the lifespan of the infected nematodes, improved behavioral impairments, decreased lipofuscin and ROS accumulation, and alleviated oxidative stress. Mechanistically, RA upregulated the expression profiles of the mev-1 and gas-1 mitochondrial-related genes involved in mitochondrial complex assembly and function. This enhanced MMP and ATP synthesis and mitigated PA14-induced mitochondrial dysfunction.DiscussionThese results indicated that RA protected C. elegans from PA14 infection via its antioxidant properties and its ability to improve mitochondrial function, highlighting its potential as a natural compound for addressing PA14 contamination.